2019
DOI: 10.1016/j.ajhg.2019.09.027
|View full text |Cite
|
Sign up to set email alerts
|

A Genocentric Approach to Discovery of Mendelian Disorders

Abstract: The advent of inexpensive, clinical exome sequencing (ES) has led to the accumulation of genetic data from thousands of samples from individuals affected with a wide range of diseases, but for whom the underlying genetic and molecular etiology of their clinical phenotype remains unknown. In many cases, detailed phenotypes are unavailable or poorly recorded and there is little family history to guide study. To accelerate discovery, we integrated ES data from 18,696 individuals referred for suspected Mendelian d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 83 publications
1
41
0
Order By: Relevance
“…Non‐paternity was ruled out through identity‐by‐descent analysis. This de novo variant was not seen in internal controls–as previously described (Hansen et al, 2019)—affects a highly conserved residue (GERP++ = 3.54, as obtained from the UCSC Genome Browser) and has a very low MTR score (21 bp window)—0.34—indicative of a region constrained for nonsynonymous variation in control populations (Davydov et al, 2010; Kent et al, 2002; Traynelis et al, 2017).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Non‐paternity was ruled out through identity‐by‐descent analysis. This de novo variant was not seen in internal controls–as previously described (Hansen et al, 2019)—affects a highly conserved residue (GERP++ = 3.54, as obtained from the UCSC Genome Browser) and has a very low MTR score (21 bp window)—0.34—indicative of a region constrained for nonsynonymous variation in control populations (Davydov et al, 2010; Kent et al, 2002; Traynelis et al, 2017).…”
Section: Resultssupporting
confidence: 56%
“…Next, we investigated the phenotypes of these two affected siblings compared to previously published and unpublished cases. We used HARLEE (Hansen et al, 2019) to search across >20,000 ES samples from the Baylor Hopkins Center for Mendelian Genomics and a clinical diagnostic lab (see Supporting Information) for cases solved by KIF1A and identified eight such cases (Table 1 and Figure 1). Phenotypes not previously known to associate with monoallelic KIF1A dysfunction were identified in multiple patients, including dystonia (4/10, 40%) and hip subluxation (3/10, 30%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For individuals 1, 6, and 8–13, DNA capture and sequencing of exomes was carried out as previously described by Hansen et al 7 at either the Baylor Genetics (BG) laboratories or at the Baylor College of Medicine Human Genome Sequencing Center (HGSC). Sequencing and analysis for individuals 2 (genome sequencing) and 5 (exome sequencing [ES]) were provided by the Broad Institute of MIT and Harvard Center for Mendelian Genomics (Broad CMG).…”
Section: Methodsmentioning
confidence: 99%
“…Modern definition of Mendelian disease is complex, with variable levels of monogenicity, penetrance (Claussnitzer et al, 2020), epistasis, gene x environment interactions and indeed pleiotropy observed (Chakravorty & Hegde, 2017). In MendelVar, we follow the working definitions from Chakravorty & Hegde (2017) and Hansen et al (2019) with broadly defined Mendelian genes to include genes causal for highly penetrant monogenic and oligogenic diseases, including diseases involving cell mosaicism, recurrent de novo structural variants causing mostly developmental diseases, such as Smith-Magenis syndrome and some germline cancer susceptibility genes such as BRCA1/BRCA2. As long as the gene-phenotype association is highly replicable, penetrant, rare, and of large effect, it increases our understanding of biological processes involved in disease pathology and augments our pool for potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%